2016
DOI: 10.1002/uog.15994
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of effects of digital vaginal examination with transperineal ultrasound during labor on pain and anxiety levels: a randomized controlled trial

Abstract: The perception of pain was significantly reduced with the use of a transperineal ultrasound assessment compared with routine digital vaginal examination. However, only during the latent stage of labor was the magnitude of the observed effect sufficiently great to be considered clinically significant. Our results indicate that transperineal ultrasound assessment could be preferred to digital examination for the evaluation of progression of labor during this phase. Digital examination has no clinically relevant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 16 publications
1
28
0
Order By: Relevance
“…Vaginal digital examination is neither highly reproducible nor reliable for determining cervical dilation and is a cause of intense emotional distress for many women during pregnancy and labor . In addition, digital vaginal examination is painful, and it has been demonstrated that transperineal ultrasound is less bothersome …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Vaginal digital examination is neither highly reproducible nor reliable for determining cervical dilation and is a cause of intense emotional distress for many women during pregnancy and labor . In addition, digital vaginal examination is painful, and it has been demonstrated that transperineal ultrasound is less bothersome …”
Section: Discussionmentioning
confidence: 99%
“…In addition, digital vaginal examination is poorly tolerated. This is evident when comparing the pain produced by digital vaginal examination with the pain produced by transperineal ultrasound …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of new techniques have been described using transperineal ultrasound to monitor labor progress through measurements relating fetal head position to the maternal pelvis 12,13 . These techniques are non-invasive, are well tolerated by patients and have a high degree of inter-and intraobserver reliability 8,[14][15][16][17][18][19][20][21][22][23] . The most widely studied measurement is that of the angle of progression (AoP), which is the angle between the leading part of the fetal skull and the maternal pubic symphysis 13 .…”
Section: Introductionmentioning
confidence: 99%
“…In this group, the average angle obtained in vaginal deliveries was 141.6º (SD 14.8, improve the comfort of the pregnant woman, compared to digital exploration [11]. Souka noted that assessment of fetal head position by digital examination, wich is dependent and poorly reproducible by another operator, was not possible in 61% of cases in the first stage and 31% in the second stage of labor [12].…”
Section: Spontaneous Vaginal Delivery Occurred In 72 (71%) Women Insmentioning
confidence: 99%